Wh-clitic-doubling and wh-Cliticisation - El Hankari, Abdelhak; Ouhalla, Jamal (IBERIA: An International Journal of Theoretical Linguistics, 2014)
This article explores a pervasive phenomenon in Berber whereby the extraction of dative arguments (of verbs, nouns and prepositions) gives rise to two occurrences of wh. One is a wh-word located in Spec,C and the other a wh-clitic in the dative form located in C (wh-clitic-doubling). Close examination reveals that the wh-word in Spec,C functions as an operator base-generated in its scope position and the dative wh-clitic in C provides it with a derivational link to the variable in the dative position it binds (wh-Cliticisation). Wh-clitic-doubling and wh-Cliticisation amount to direct evidence for Cliticisation as a derivational interpretive mechanism of Grammar that obviates the need for indexing (Lebeaux 1983, Chomsky 1986, 1995). They also provide evidence for the conclusion in Kayne (1989) that Cliticisation is an instance of Head-Movement, more precisely, feature-based Head-Movement.